Music Education in the Senior Secondary Schools in Nigeria: An Overview and the Experience - Ajewole, John (NIU Journal of Educational Research, 2024)
The objective of this paper is to examine the current state of music education in Nigerian Senior Secondary Schools and how music teachers will adopt an effective transformation in music education at all levels in Senior Secondary Schools. This study is to enable music teachers /educators to reposition and re-strategize themselves for the development of music education in Nigerian schools. The survey method is very useful to this study. There are three aspects to survey methods as used in the study. These are: (1) observation, (2) interview, and (3) questionnaire. One hundred (100) senior secondary schools (SSS) students from five different secondary schools including public, private girls only, boys only, and co-educational found within Ibadan municipality of Oyo State, Nigeria, and situated in different local governments (Ibadan North, Ibadan North-East and Ibadan South-West) were used for the study. The outcome of the study shows that the bias of government educational policies in favour of core science and science-based disciplines is a significant issue that will continue to affect the listing of music as a core- subject in Junior and Senior Secondary schools. Nigerian music teachers have continually agitated for better funding of the music program in the school systems by the government and its agencies. In recent times, the teaching of music in Nigerian schools was incorporated and merged into the CCA program. It is realized in this new curriculum that the four (4) different areas of study are merged to form a subject called CCA: fine art, music, drama, and craft.  For music education in Nigeria to improve in standard and output, it should be given a solid foundation at the Nursery/Primary school level. In conclusion, all the above aims of music education cannot be achieved unless there are enough professionally trained, efficient, committed, and effective teachers. It is necessary to lay much emphasis on the training of music education teachers, products of which will be responsible for the implementation of the aims and objectives of music education programs in the pre-primary, primary, secondary, and tertiary institutions in Nigeria.  Keywords: Music, Education, Secondary, Schools, Experience.